2019
DOI: 10.3390/su11041086
|View full text |Cite
|
Sign up to set email alerts
|

Brand Equity and Firm Sustainable Performance: The Mediating Role of Analysts’ Recommendations

Abstract: Current literature has overlooked the signaling effects of the brand on a firm’s sustainable performance through financial analysts. This study posits that financial analysts may serve as the information bridge connecting brand equity and a firm’s sustainable performance by providing professional recommendations of stock investments to public investors. Using a longitudinal archived dataset of Chinese listed firms, we found that: (1) brand equity improves the level of analysts’ recommendations for a focal firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 70 publications
(129 reference statements)
0
17
0
3
Order By: Relevance
“…They also find that analysts who have private information have stronger recommendations. Hinze and Sump (2019), in their review, find that many existing literature confirm the positive relationship between CSR performance and optimistic recommendations, and Wang and Jiang (2019) show that analysts' recommendations mediate the relationship between brand equity and sustainable performance in Chinese listed firms.…”
Section: Hypotheses Developmentmentioning
confidence: 96%
“…They also find that analysts who have private information have stronger recommendations. Hinze and Sump (2019), in their review, find that many existing literature confirm the positive relationship between CSR performance and optimistic recommendations, and Wang and Jiang (2019) show that analysts' recommendations mediate the relationship between brand equity and sustainable performance in Chinese listed firms.…”
Section: Hypotheses Developmentmentioning
confidence: 96%
“…As discussed, brands can create values, and values are developing or evolving over time, this expansion represents the sustainable characteristic of brands. Based on existing literature, we argued that brand equity is one of the major affecting elements on the sustainable performance of companies that brand owners should consider [18][19][20], having said that, the current research framework is proposed. The major objective of the present study is to analyze the sustainable relationship between the concepts of brand equity and purchase intention mediated through price premium and brand preference.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Brand equity is considered marketing's core concept [6,16,17] and appears when consumers are familiar with certain brands resulting in reliable and unique brand associations in their minds. Brand equity has been widely recognized as a significant factor affecting the sustainable performance of companies by marketing practitioners and scholars [4,[18][19][20]. Although there are numerous studies and definitions regarding brand equity [21][22][23], these definitions are either customer-based and/or financial-based perspectives [24,25].…”
Section: Brand Equity (Be)mentioning
confidence: 99%
“…Previous studies have suggested that firm size has an impact on firm value because large firms are better at managing their risks than small ones, which helps them to avoid threats to their value [62,63]. Firm age (AGE) is measured as the number of years since the establishment of a listed firm [64]. Prior studies demonstrate that younger firms have worse firm performance than older ones because of lack of experience, external connections, and legitimacy [65,66].…”
Section: Methodsmentioning
confidence: 99%